Multicomponent synthesis of unsymmetrical derivatives of 4-methyl-substituted 5-nitropyridines - Turgunalieva, Daria M.; Stalinskaya, Alena L.; Kulakov, Ilya I.; Sagitullina, Galina P.; Atuchin, Victor V.; Elyshev, Andrey V.; Kulakov, Ivan V. (Processes)
The multicomponent reaction of 2-nitroacetophenone (or nitroacetone), acetaldehyde diethyl acetal, β-dicarbonyl compound, and ammonium acetate in an acetic acid solution allowed the acquisition of previously undescribed 4-methyl-substituted derivatives of 5-nitro-1,4-dihydropyridine in satisfactory yields. The oxidation of the obtained 5-nitro-1,4-dihydropyridine derivatives resulted in the corresponding 2,4-dimethyl-5-nitropyridines. In addition, for the first time in the synthesis of unsymmetrical 1,4-dihydropyridines by the Hantzsch reaction acetaldehyde, diethyl acetal was used as a source of acetaldehyde. The use of more volatile and sufficiently reactive acetaldehyde in this reaction did not lead to a controlled synthesis of unsymmetrical 5-nitro-1,4-dihydropyridines. The proposed multicomponent approach to the synthesis of 4-methyl-substituted 5-nitro-1,4-dihydropyridines and their subsequent aromatization into pyridines made it possible to obtain previously undescribed and hardly accessible substituted 5(3)-nitropyridines.